Farming Systems Research: Clarification of Terms and Concepts - Merrill-Sands, Deborah (Cambridge University Press, 1986)
Farming Systems Research (FSR) has emerged as a major theme in international agricultural research in the past decade. However, despite widespread use of the term, its meaning and the types of research objectives, approaches, activities and methods to which it applies remain ambiguous. The lack of precision in concepts and terms will discredit FSR and jeopardize donor support. This paper seeks to clarify and define the major types of research approaches and activities encompassed by the general term FSR. Six types of research are distinguished and a new, more precise terminology is proposed.